169 BODY MASS INDEX, INSULIN RESISTANCE INDICES AND LIPID PROFILE THEIR RELATIONSHIP WITH HIGHLY SENSITIVE C - REACTIVE PROTEIN IN OBESE CHILDREN. (1st January 2005) - Evans, W. N.; Mayman, G. A.; Acherman, R. J.; Cass, K. A; Kip, K. T.; Luna, C. F.; Rothman, A.; Coviello, L.; Gustafson, A.; Restrepo, H.
Abstract : Background: In adults, C-reactive protein has been used as a putative biomarker of chronic inflammation and potential predictor of adverse cardiovascular outcomes associated with insulin resistance (IR) in obesity. Elevated levels of C-reactive protein have been reported positively associated with body mass index (BMI) in children. Objectives: To assess the relationship between highly sensitive C-reactive protein (hs-CRP) with BMI, insulin resistance indices and lipid profile in non-diabetic obese children. Methods: The study included118 overweight (BMI ≥ 95th percentile), and non-diabetic children referred to our risk factor reduction program from February 2003 to May 2004. Hs-CRP, lipid profile, fasting glucose and fasting insulin levels were obtained. BMIs were assessed using 2000 CDC growth charts. Two indices of IR were calculated: Quicki (1/(log insulin + log glucose)) and glucose/insulin ratio, also triglycerides/HDL-cholesterol ratio (Tg/HDL-c ratio) was calculated. Results: There were, 69 males (58.5 %), and 49 females (41.5 %). Mean age was 11.2 years (range: 5-18 years). Mean BMI Z-score: +2.4 (SD: 0.34). Mean hs-CRP: 4.44 mg/L (SD: 6.4). Mean hs-CRP did not differ between sexes. There was not found any significant correlation between hs-CRP and insulin resistance indices, lipid profile, Tg/HDL-c ratio, BMI or age. Conclusions: Our data show that in obese children the mean hs-CRP is elevated but not related to BMI, insulin resistance indices, lipid profile, Tg/HDL-c ratio or age